Optimization of Bandwidth Management Using Y.1731 Method Based on Ethernet OAM on Raisecom Devices in Metro Ethernet Networks - Muhamad Rafli Alfiansyah; Nandang Sutisna (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The growing demand for reliable Quality of Service (QoS) in Metro Ethernet networks has highlighted the need for a bandwidth management approach that is both standardized and efficient. This research explores the optimization of bandwidth configuration through the implementation of the ITU-T Y.1731 protocol, which operates within the framework of Ethernet Operations, Administration, and Maintenance (OAM). A network simulation was carried out using the Enterprise Network Simulation Platform (eNSP) with Huawei devices, serving as a functional equivalent of Raisecom equipment. The study employed a quantitative experimental method, involving the design and configuration of a Metro Ethernet topology, the deployment of Connectivity Fault Management (CFM), and the activation of performance monitoring mechanisms such as Delay Measurement Message (DMM) and Loss Measurement Message (LMM). Key performance indicators analyzed included delay, jitter, and packet loss, observed before and after the Y.1731 implementation. The findings reveal that the application of Y.1731 improved bandwidth utilization efficiency by up to 25%, reduced average delay, minimized jitter, and produced measurable data for validating Service Level Agreement (SLA) compliance. Overall, the integration of Y.1731 into Metro Ethernet networks based on Huawei devices demonstrates a practical and effective solution for strengthening service performance and ensuring network reliability.